PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - Romadhoni Romadhoni; Hadi Sunaryo (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT This study aims to determine the effect of Debt Equity Ratio, Debt to Asset Ratio and Equity to Asset Ratio partially and together to Return on Equity. Debt Equity Ratio, Debt to Asset Ratio, Equity to Asset Ratio as independent variable and Return on Equity as dependent variable. The type of research used is empirical, population in this research is food and beverage Manufacturing company listed in Indonesia Stock Exchange period 2013-2016 with purposive sampling technique. Sample amounts to Twelve Manufacturing Companies food and beverage sector. The data analysis used is multiple linear regression and classical assumption test. Debt to Asset Ratio has value t count -0,965 (sig 0,340> 0,05) Equity to Asset Ratio has value of t count 0,942 (sig. 0.351> 0.05) indicating that Debt Equity Ratio partially have a significant positive effect, Debt to Asset Ratio and Equity to Asset Ratio partially have no significant effect to Equity to Asset Ratio. As well as bersam-sma Debt Equity Ratio, Debt to Asset Ratio and Equity to Asset Ratio have a significant positive effect on Return on Equity. Demonstrated with large F arithmetic 3,444 (sig. 0.008 <0.05). Keywords: Debt Equity Ratio, Debt to Asset Ratios, Equity to Assets and Return on Equity.